1997
DOI: 10.1177/001872679705001204
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Models for Antecedents and Outcomes of Work Centrality and Job Satisfaction of High-Tech Personnel

Abstract: Alternative causal models were developed, relating Work Centrality and Job Satisfaction to antecedents and outcomes. The antecedents examined were demographics and need for achievement, and the outcomes included performance, wages, organizational commitment, and career planning. The models were tested using data of Israeli high-tech personnel. Results indicated that organizational commitment, career planning, and wages were significantly affected by work centrality, while performance was positively but nonsign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
2
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 56 publications
5
79
2
1
Order By: Relevance
“…First, by showing that work centrality is related to positive attitudes towards the job, this study contributes to the literature on work centrality, which is mainly focused on antecedents of work centrality (Mannheim, Baruch, & Tal, 1997). In addition to organization citizenship behavior, career satisfaction, and organization commitment (Aryee & Luk, 1996;20 Diefendorff et al, 2002;Witt et al, 2002), work centrality was found to influence job satisfaction, work engagement, and turnover intention.…”
Section: Discussionmentioning
confidence: 70%
“…First, by showing that work centrality is related to positive attitudes towards the job, this study contributes to the literature on work centrality, which is mainly focused on antecedents of work centrality (Mannheim, Baruch, & Tal, 1997). In addition to organization citizenship behavior, career satisfaction, and organization commitment (Aryee & Luk, 1996;20 Diefendorff et al, 2002;Witt et al, 2002), work centrality was found to influence job satisfaction, work engagement, and turnover intention.…”
Section: Discussionmentioning
confidence: 70%
“…For instance, Curry, Wakefield, Price and Mueller (1986) found no significant relationship between job satisfaction and organizational commitment. However, other researchers (Busch et al, 1998;Chiu-Yueh, 2000;Feinstein & Vondraek, 2006;Freund, 2005;Mannheim et al, 1997) found that job satisfaction was a significant predictor of organizational commitment. Some researchers argued that job satisfaction reflects immediate affective reactions to the job while commitment to the organization develops more slowly after the individual forms more comprehensive valuations of the employing organization, its values, and expectations and one's own future in it.…”
Section: Job Satisfaction and Organizational Commitment In Institutiomentioning
confidence: 94%
“…Some researchers argued that job satisfaction reflects immediate affective reactions to the job while commitment to the organization develops more slowly after the individual forms more comprehensive valuations of the employing organization, its values, and expectations and one's own future in it. Therefore, job satisfaction is seen as one of the determinants of organizational commitment (Mannheim et al, 1997). It is thus expected that highly satisfied workers will be more committed to the organization.…”
Section: Job Satisfaction and Organizational Commitment In Institutiomentioning
confidence: 99%
“…Salanova et al (2003) used an objective measure of task performance in their study of teams. Performance appraisal data are high quality, yet are difficult to obtain (Huselid & Day, 1991;Mannheim, Baruch, & Tal, 1997). A typical alternative approach is to gather self-ratings of performance.…”
Section: Performancementioning
confidence: 99%